Sustainable Pest Management in Date Palm: Current Status and Emerging Challenges - Miller, Thomas A; Romeno Faleiro, Jose; Wakil, Waqas (2015)
Date palm, Phoenix dactylifera L. (Arecales: Arecaceae), is an important palm species cultivated since pre-historic times in the arid regions of the world and traditionally associated with the life and culture of the people in the Middle-East and North Africa which are the pre-dominant date palm growing regions worldwide. The crop is currently cultivated in nearly 30 countries in the Asian, African, American and Australasian continents. The Food and Agriculture Organization of the UN estimates that there are over 100 million date palms world wide with an annual production of over 7.5 million tonnes Date palm is attacked by a wide range of insect pests mainly from the orders Coleoptera, Lepidoptera and Hemiptera besides phytophagous mites, several of which cause substantial loss in yield and even mortality of palms. During the last two decades there has been a significant increase in date palm cultivation worldwide especially in the Middle-East and North Africa where the area has increased over 50%, mostly in vast stretches of monoculture plantations offering a conducive macro and micro ha bitat for existing and emerging insect pests of date palm. Global warming together with rapid large scale movement of palm species for farming and ornamental gardening has compounded the threat of insect pests to date palm. Indiscriminate use of insecticides to control these pests as the first line of defense is of major concern in the date growing countries due to the inherent disadvantages of insecticidal residues in dates (affecting exports), development of resistance to insecticides in the target species and resurgence of minor pest to major insect pest associated with chemical control The book provides an overview on the biology (life cycle, damage, losses, geographical distribution, host range) and management (monitoring, action thresholds, biological control, chemical control, mechanical control, use of semiochemicals and biopesticides) of major arthropod pests of date palm from the orders Coleoptera (red palm weevil, long horn beetle, rhinoceros beetle, frond borer, sap beetles), Hemiptera (dubas bug, issid bug, scale insects, mealy bug) and Lepidoptera (lesser date moth, carob moth, raisin moth), and mites. The issues pertaining to the role of semiochemicals in date pest management and innovative methods for managing storage pests of dates are also addressed. The book on date palm IPM will serve as a document for farmers, students, researchers and administrators involved in the date palm industry.
Keywords: Agriculture; Entomology; Plant pathology; Agriculture; Entomology; Plant Pathology